Tumor-Volume Changes after Radiosurgery for Vestibular Schwannoma: Implications for Follow-Up MR Imaging Protocol - Meijer, O.W.M.; Weijmans, E.J.; Knol, D.L.; Slotman, B.J.; Barkhof, F.; Vandertop, W.P.; Castelijns, J.A. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: The outcome of radiosurgery for vestibular schwannoma (VS) is assessed by posttreatment measurement of tumor size and could be influenced by the timing and quality of the assessment. This study evaluates the volumetric changes of VS after radiosurgery and proposes a radiologic follow-up program.MATERIALS AND METHODS: Of 142 patients with VS treated with radiosurgery, we selected patients who were followed at least 3 times during a minimum of 32 months with a T1-weighted gadolinium-enhanced high-resolution 3D MR imaging examination identical to the pretreatment MR imaging. Forty-five patients were identified with a mean follow-up of 50 months (range, 32–78 months). Pre- and posttreatment tumor volumes were calculated by using BrainSCAN software by manually contouring tumors on each MR imaging study. Volume changes of >13% were defined as events.RESULTS: At last follow-up MR imaging, volumes were smaller in 37 (82.2%) of the 45 patients. Eleven (29.7%) of these 37 tumors showed transient swelling preceding regression, with a median time to regression of 34 months (range, 20–55 months). Seven (15.6%) of the 45 tumors had volume progression compared with the tumor on pretreatment MR imaging studies. Of these 7 tumors, 3, however, had volume regression compared with the preceding MR imaging study, and in 4, volume progression was ongoing. One tumor remained the same.CONCLUSIONS: Tumor-volume measurements by standardized T1-weighted gadolinium-enhanced high-resolution 3D MR imaging follow-up protocols revealed good local control of VS after radiosurgery. The first-follow-up MR imaging at 2 years and the second at 5 years postradiosurgery differentiated transient progression from ongoing progression and may prevent unnecessary therapeutic interventions.